2018
DOI: 10.1177/1363461518764491
|View full text |Cite
|
Sign up to set email alerts
|

Cultural expressions of depression and the development of the Indonesian Depression Checklist

Abstract: Depression may manifest differently across cultural settings, suggesting the value of an assessment tool that is sensitive enough to capture these variations. The study reported in this article aimed to develop a depression screening tool for Indonesians derived from ethnographic interviews with 20 people who had been diagnosed as having depression by clinical psychologists at primary health centers. The tool, which we have termed the Indonesian Depression Checklist (IDC), consists of 40 items. The tool was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
0
6
0
3
Order By: Relevance
“…A large proportion of the locally-appropriate measures of mental health which have been developed up to now have attempted to identify and measure clinical disorders or syndromes [ 11 , 15 , 20 ],. The study described here does not follow this pattern; instead it aims to measure ‘signs of distress’ without drawing any conclusions about clinical significance, or trying to equate experiences of distress with clinical diagnoses such as depression, anxiety of post-traumatic stress disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large proportion of the locally-appropriate measures of mental health which have been developed up to now have attempted to identify and measure clinical disorders or syndromes [ 11 , 15 , 20 ],. The study described here does not follow this pattern; instead it aims to measure ‘signs of distress’ without drawing any conclusions about clinical significance, or trying to equate experiences of distress with clinical diagnoses such as depression, anxiety of post-traumatic stress disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Some 35 years ago, Kleinman [ 9 ] suggested that local idioms of depression be translated and added to standard questionnaires, and subsequently, researchers have emphasised the importance of including locally salient concepts and phrases in tools to measure psychological distress and mental health disorders [ 10 ]. As a result, local assessment tools have been developed in various settings to enable more accurate assessments of psychological distress [ 11 ]. These local assessment instruments have been found to be more effective measures of mental disorders than international instruments in various populations [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salah satu alat asesmen depresi yang disusun dengan mempertimbangkan budaya Indonesia adalah Indonesian Depression Checklist (IDC). IDC disusun berdasarkan pengalaman depresi pada pasien di Puskesmas di Kabupaten Sleman dan Kota Yogyakarta dan memiliki validitas kriteria yang baik pada populasi umum (Widiana, Simpson, & Manderson, 2018). Validitas konkuren merupakan salah satu tipe validitas kriteria yang menguji kesesuaian hasil ukur satu alat ukur dengan alat ukur lain yang relevan dan sudah teruji kualitas psikometrisnya (Azwar, 2018).…”
Section: Pendahuluanunclassified
“…Oleh karenanya diperlukan adanya alat ukur tepat secara budaya dalam proses asesmen depresi. IDC merupakan alat skrining depresi yang mengakomodir faktor budaya dalam manifestasi depresi (Widiana et al, 2018). IDC terdiri dari lima aspek, salah satunya yaitu mengenai aktivitas religius yang tidak diikutkan dalam asesmen depresi.…”
Section: Hasil Dan Pembahasanunclassified
“…Studies have found important variance in the ways that people express distress in different contexts (e.g. Keys et al ., 2012; Haroz et al ., 2017; Widiana et al ., 2018; Housen et al ., 2019). Yet, the assumption noted by Kleinman (1977), that because phenomena can be identified in different cultural settings they have the same meaning across these settings, continues to be evident in many studies.…”
Section: Introductionmentioning
confidence: 99%